Optimal AoI for Systems With Queueing Delay in Both Forward and Backward Directions - Wang, Chih-Chun (IEEE/ACM transactions on networking, 2024)
Age-Of-Information (AoI) is a metric that focuses directly on the application-layer objectives, and a canonical AoI minimization problem is the update-through-queues models. Existing results in this direction fall into two categories: The open-loop setting for which the sender is oblivious of the packet departure time, versus the closed-loop setting for which the decision is based on instantaneous Acknowledgment (ACK). Neither setting perfectly reflects modern networked systems, which almost always rely on feedback that experiences some delay. Motivated by this observation, this work subjects the ACK traffic to a second queue so that the closed-loop decision is made based on delayed feedback. Near-optimal schedulers have been devised, which smoothly transition from the instantaneous-ACK to the open-loop schemes depending on how long the feedback delay is. The results quantify the benefits of delayed feedback for AoI minimization in the update-through-queues systems.